2018
DOI: 10.1101/357350
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seroprevalence of fourteen human polyomaviruses determined in blood donors

Abstract: 10The polyomavirus family currently includes thirteen human polyomavirus (HPyV)

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 38 publications
3
3
0
Order By: Relevance
“…Our results on prevalence and persistence of MCPyV, HPyV6, and HPyV7 are in concordance with serological studies in healthy individuals that found antibodies against MCPyV, HPyV6, and HPyV7 capsid proteins in 81.9, 83.8, and 71.7% of healthy blood donors, respectively (Kamminga et al, 2018). TSPyV-and HPyV9-specific antibodies were detected in 80-90% and >30-70%, respectively, and primary infection seems to occur during early childhood and adolescence (Foulongne et 2012;Nicol et al, 2013;Kamminga et al, 2018). Hence, it is possible that the skin is not the only tissue infected by these viruses.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Our results on prevalence and persistence of MCPyV, HPyV6, and HPyV7 are in concordance with serological studies in healthy individuals that found antibodies against MCPyV, HPyV6, and HPyV7 capsid proteins in 81.9, 83.8, and 71.7% of healthy blood donors, respectively (Kamminga et al, 2018). TSPyV-and HPyV9-specific antibodies were detected in 80-90% and >30-70%, respectively, and primary infection seems to occur during early childhood and adolescence (Foulongne et 2012;Nicol et al, 2013;Kamminga et al, 2018). Hence, it is possible that the skin is not the only tissue infected by these viruses.…”
Section: Discussionsupporting
confidence: 91%
“…This notion is supported by several studies, in which TSPyV and HPyV9 were detected sporadically in tonsil tissue, faeces, respiratory samples, urine or peripheral blood, mainly in immunosuppressed persons (Rockett et al, 2013;Herberhold et al, 2017;Kourieh et al, 2018;Borgogna et al, 2019;Kamminga et al, 2019). In our study, short-term persistence rates of HPyV10 were low and long-term persistence did not occur, although HPyV10 reaches a seroprevalence rate of nearly 100% in adults (Kamminga et al, 2018). This indicates that the skin is only transiently infected and does not represent a permanent viral reservoir of HPyV10.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations